Keputusan Pembelian Produk Kecantikan di TikTok Shop: Peran Perceived Value, E-WOM, dan Perceived Ease of Use bagi Generasi Z - Sandira, Nur Fadilah Ayu; Iswardhani, Indri; Macenning, A. Reski Almaida dg; Sarah, Nulthazam; Nasir, Sri Astuti (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study aims to analyze the influence of Perceived Value, E-WOM (Electronic Word of Mouth), and Perceived Ease of Use on purchasing decisions of beauty products on TikTok Shop, specifically among Generation Z in Makassar. Using a quantitative method with a descriptive approach and survey, data was collected through questionnaires from 105 respondents, TikTok users in Makassar who have purchased beauty products on the platform. The findings reveal that all three factors have a significant positive impact on purchasing decisions. High Perceived Value encourages purchases as consumers feel the product is worth the price. E-WOM, originating from recommendations by other users, enhances trust and purchase interest. Meanwhile, Perceived Ease of Use, which includes ease of transaction, contributes to consumer comfort while shopping. Overall, these three factors work together to create a positive shopping experience and influence purchasing decisions for beauty products on TikTok Shop.